2018
DOI: 10.1038/s41385-018-0073-9
|View full text |Cite
|
Sign up to set email alerts
|

IL-17-dependent SIgA-mediated protection against nasal Bordetella pertussis infection by live attenuated BPZE1 vaccine

Abstract: BPZE1 is a live attenuated Bordetella pertussis vaccine for nasal administration to mimic the natural route of infection. Here, we studied the mechanism of BPZE1-induced immunity in the murine nasal cavity in contrast to acellular vaccine (aPV), although both vaccines protected against lung colonization. Transfer of splenocytes or serum from BPZE1-vaccinated or aPV-vaccinated mice protected naïve mice against lung colonization but not against nasal colonization. However, transfer of nasal washes from BPZE1-vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 47 publications
3
92
1
Order By: Relevance
“…Live vaccines have the potential to induce strong mucosal protection, but suffer from concern about their risk. An exciting new vaccine candidate against B. pertussis is the live attenuated vaccine, BPZE1, which has been shown to induce a robust local B and T cell response despite genetically engineered mutations that render it relatively safe (283,284). Excitingly, phase I trials demonstrate that the intranasal formulation of the vaccine transiently colonizes the nasal cavity, leading to the generation of stronger immunity (264,268).…”
Section: Novel Vaccination Strategiesmentioning
confidence: 99%
“…Live vaccines have the potential to induce strong mucosal protection, but suffer from concern about their risk. An exciting new vaccine candidate against B. pertussis is the live attenuated vaccine, BPZE1, which has been shown to induce a robust local B and T cell response despite genetically engineered mutations that render it relatively safe (283,284). Excitingly, phase I trials demonstrate that the intranasal formulation of the vaccine transiently colonizes the nasal cavity, leading to the generation of stronger immunity (264,268).…”
Section: Novel Vaccination Strategiesmentioning
confidence: 99%
“…A parallel study also, found that after the fifth dose of DTaP the odds of acquiring pertussis increased on average 42% each year 35 . This trend continued as the same group compared pertussis rates among adolescents who received the Tdap booster, which consists of a lower concentration of vaccine antigens with the addition of Fim antigen.…”
Section: Waning Dtap Vaccinementioning
confidence: 89%
“…Vaccine potency was assessed as international units, determined by comparing mouse survival following different lots of wPs compared to survival following a standard vaccine. The problem was that DTaP vaccine-induced protection could not be fully validated using Kendrick's mouse potency test, as DTaP immunizations did not protect against lethality in the intracerebral challenge 25 . To address this, a modified Kendrick test was developed to assess vaccine potency of DTaP immunizations 26 .…”
Section: History Of B Pertussis Vaccination and The Increase In B Pmentioning
confidence: 99%
See 2 more Smart Citations